No impact of sex and age on beta‐adrenoceptor‐mediated inotropy in human right atrial trabeculae. (29th October 2020) - Pecha, Simon; Geelhoed, Bastiaan; Kempe, Romy; Berk, Emanuel; Engel, Andreas; Girdauskas, Evaldas; Reichenspurner, Hermann; Ravens, Ursula; Kaumann, Alberto; Eschenhagen, Thomas; Schnabel, Renate B.; Christ, Torsten
Abstract: Aim: There is an increasing awareness of the impact of age and sex on cardiovascular diseases (CVDs). Differences in physiology are suspected. Beta‐adrenoceptors (beta‐ARs) are an important drug target in CVD and potential differences might have significant impact on the treatment of many patients. To investigate whether age and sex affects beta‐AR function, we analysed a large data set on beta‐AR‐induced inotropy in human atrial trabeculae. Methods: We performed multivariable analysis of individual atrial contractility data from trabeculae obtained during heart surgery of patients in sinus rhythm (535 trabeculae from 165 patients). Noradrenaline or adrenaline were used in the presence of the beta2 ‐selective antagonist (ICI 118 551, 50 nmol/L) or the beta1 ‐selective antagonist (CGP 20712A, 300 nmol/L) to stimulate beta1 ‐AR or beta2 ‐AR respectively. Agonist concentration required to achieve half‐maximum inotropic effects (EC50 ) was taken as a measure of beta‐AR sensitivity. Results: Impact of clinical variables was modelled using multivariable mixed model regression. As previously reported, chronic treatment with beta‐blockers sensitized beta‐AR. However, there was no significant interaction between basal force, maximum force and beta‐AR sensitivity when age and sex were modelled continuously. In addition, there was no statistically significant effect of body mass index or diabetes on atrial contractility. Conclusion: Our large, multivariable analysis shows that neither age nor sex affects beta‐AR‐mediated inotropy or catecholamine sensitivity in human atrial trabeculae. These findings may have important clinical implications because beta‐ARs, as a common drug target in CVD and heart failure, do not behave differently in women and men across age decades.